2014
DOI: 10.1139/cjfr-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses to arbuscular mycorrhizal fungi and salt stress in dioecious plantPopulus tomentosa

Abstract: This study elucidated whether the beneficial effect of arbuscular mycorrhizal (AM) symbiosis was different in male and female Populus tomentosa Carrière trees. Female and male cuttings of P. tomentosa were treated with two AM fungal regimes, with or without an AM fungus (Glomus constrictum Trappe) inoculation, and with three salt regimes, no salt, low-salinity level (100 mmol·L–1 NaCl), and high-salinity level (200 mmol·L–1 NaCl). Our results showed that AM fungal colonization alleviated the salt-induced reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
7
10
0
1
Order By: Relevance
“…With a reduction in RWC, a loss of turgor results in a limitation in the water available for cell expansion processes. Our results for the series of plant responses to salt stress were consistent with most studies: the limitation of salt on growth diameters3132. However, the responses to salt stress and AMF inoculation differed between males and females: Females showed a higher GH than males without AMF inoculation in the absence of NaCl, while males showed a higher GH than females with AMF inoculation under saline conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With a reduction in RWC, a loss of turgor results in a limitation in the water available for cell expansion processes. Our results for the series of plant responses to salt stress were consistent with most studies: the limitation of salt on growth diameters3132. However, the responses to salt stress and AMF inoculation differed between males and females: Females showed a higher GH than males without AMF inoculation in the absence of NaCl, while males showed a higher GH than females with AMF inoculation under saline conditions.…”
Section: Discussionsupporting
confidence: 90%
“…However, the responses to salt stress and AMF inoculation differed between males and females: Females showed a higher GH than males without AMF inoculation in the absence of NaCl, while males showed a higher GH than females with AMF inoculation under saline conditions. This suggested that AMF had different impact on the two genders, as described by Lu et al 32. and Li et al 2021…”
Section: Discussionmentioning
confidence: 70%
“…The lower levels of Na + in AMF-inocualted plants have also been reported in many previous studies (Evelin et al 2012;Lu et al 2014;Pollastri et al 2018). However, Allen and Cunningham (1983) indicated that AMF can occassionally enhance Na + uptake, suggesting that AMF could induce a buffering effect on the uptake of Na + causing higher Na + concentration in mycorrhizal plants at low salinity and lower Na + concentration at higher salinity.…”
Section: Effects Of Amf Inoculation On Ion Contents and Ion Balances supporting
confidence: 83%
“…3c). Many studies have reported higher antioxidant enzymes activities in AMF-inoculated plants, when compared with those in non-inoculated plants (Hajiboland et al 2010;Lu et al 2014). In the present study, higher activities of antioxidant enzymes (POD, CAT, and SOD) were observed in AMF-inoculated plants, especially in roots, when compared with those in non-inoculated plants.…”
Section: Effects Of Amf Inoculation On Osmotic Adjustment Under Salinsupporting
confidence: 56%
“…AMF are mutually symbiotic and provide a direct physical link between the soil and plant roots (Gaur & Adholeya 2004). AMF promotes salinity tolerance by increasing nutrient uptake (Evelin et al 2012, Beltrano et al 2013, improving rhizospheric and soil conditions (Asghari et al 2005), increasing photosynthesis and water use efficiency (Hajiboland et al 2010), the accumulation of compatible solutes (Evelin et al 2012) and enzymatic antioxidants such as superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) as a defense system to protect the plant cell from oxidative stress (Wu et al 2010, Lu et al 2014.Funneliformis mosseae (FM) is an arbuscular mycorrhiza used to alleviate salt stress in Arachis hypogaea (Al-Khaliel 2010) …”
mentioning
confidence: 99%